Synthesis and characterization of complex metal hydrides for hydrogen technology - Nitsche, David Martin, author; Manivannan, Venkatesan, advisor; Wu, Mingzhong, committee member (Colorado State University. Libraries, 2010)
The limitation as well as the environmental impact of fossil fuels has encouraged the development of alternative energies. As an alternative, hydrogen and its applications have been established due to its favorable physical and chemical properties. Production as well as storage of hydrogen is seen to be key challenges to for a transition to a hydrogen based infrastructure. A possible storage method is seen to be chemical hydrides, where hydrogen is chemically bonded to matrix materials and can be controllable released. The chemical synthesis of these hydrides can become complex with increasing hydride structures. Therefore, mechanochemical synthesis methods have been developed, which simplify the synthesis process. The material characteristics are being determined with an XRD apparatus as well as TGA and DSC analysis. In the present study, hydrides with the general composition MH, MH2, MAlH4, and MAlH6 have been synthesized and tested for desorption characteristics, where M stands for Li, Na, K, Ca, Mg, and Ti. Doping of the materials is being applied to improve desorption characteristics of the material, where catalyst materials are implemented into the hydride structure and cause a change in the structural composition linked with a decrease of the hydrogen desorption temperature.
Department Head: Allan Thomson Kirkpatrick.